Modification of Newton's method applied to the solution of coordinate-route tasks using the passive automatic complex for the air targets tracking - Ткаченко, В.Н.; Коротков, В.В.; Пантеев, Р.Л. (Radiotekhnika, 2012)
The solution of nonlinear differential equations describing the trajectory of the radiation source based on the difference of signal arrival time delay to the receiving stations is considered. Approaches to such systems on the basis of Newton's method various modifications, taking into account different options of convergence, are studied and their effectiveness is evaluated.